The Use of Online Cheating Tools during Online Assessment in Philippine Private Higher Education Institutions - Palama, Jan Cynth L.; Marcial, Dave E. (Silliman Journal, 2025)
The transition to online learning has introduced significant challenges regarding academic integrity, as students utilize various online tools to circumvent traditional monitoring mechanisms. This study investigates the prevalence and types of online cheating tools used by Computer Studies education students during assessments in private higher education institutions in the Philippines. The primary purpose is to determine the relationship between online cheating tools and the respondents’ demographic, academic, and technological profiles. Utilizing a descriptive-correlational design, data were collected from third and fourth-year students via a self-administered survey questionnaire distributed online. The questionnaire included sections on demographic information, technological profile, and online tool usage during assessments. The results revealed that students admitted to engaging in various forms of online cheating, with the most common tools being search engines, digital calculators, AI tools, and other software to access unauthorized online resources. The analysis revealed that students with higher technological proficiency were more likely to cheat, indicating a significant correlation between familiarity with online tools and the tendency to engage in dishonest practices. Additionally, students who perceived online assessments as less engaging and challenging reported higher instances of cheating. The implications of these findings suggest a critical need for institutions to reassess and redesign their online assessment policies to combat academic dishonesty. Enhancing monitoring mechanisms, revising academic policies, and increasing student engagement through interactive and meaningful online activities are essential. Furthermore, promoting a culture of academic integrity by clearly communicating policies and consequences and providing support systems for students facing challenges in online learning is crucial. These measures could significantly mitigate the prevalence of cheating and enhance the overall quality and credibility of the online education system.